Phylogenetics of Leptocereus (Cactaceae) on Hispaniola: clarifying species limits in the L. weingartianus complex and a new species from the Sierra de Bahoruco - Majure, Lucas C.; Encarnación, Yuley; Clase, Teodoro; Peguero, Brígido; Ho, Kelly; Barrios, Duniel (PhytoKeys, 2021)
The Antillean genus Leptocereus represents an in-situ radiation among the Greater and Lesser Antilles of 19 currently recognized species. Extensive fieldwork carried out in the Dominican Republic over recent years has revealed that the species limits of Leptocereus of Hispaniola are more complex than previously thought. There are four currently recognized species that occur on the island, L. demissus , L. paniculatus , L. undulosus and L. weingartianus . We evaluate species limits in this group based on DNA sequence data and phylogenetic analysis, morphological characters and a survey of herbarium specimens from across Hispaniola. Based on our analyses, it is clear that at least five species occur on the island of Hispaniola, with the new species from Sierra de Bahoruco, L. velozianus , described here. We provide an identification key, distribution maps and photographic plates for all species on Hispaniola based on our own fieldwork and the study of herbarium specimens. The description of yet another species of Leptocereus on Hispaniola reiterates the importance of the poorly studied, but yet biodiverse, seasonally dry tropical forest in the Antilles.